The Tigris Frontier from Sargon to Hammurabi. A Philological and Historical Synthesis - Walker, Marcie Finkel (1985)
Ph.D. Dissertation; Adviser: William W. Hallo. Order No. DA8613633; cf. DissAbstr 47/04 (October 1986) 1304-A; cf. 48:740.